Copper and Nickel Coating of Carbon Fiber for Thermally and Electrically Conductive Fiber Reinforced Composites - Bard, Simon (Polymers (Basel), 2019)
In this paper, the thermal and electrical conductivity and mechanical properties of fiber reinforced composites produced from nickel- and copper-coated carbon fibers compared to uncoated fibers are presented. The carbon fibers were processed by our prepreg line and cured to laminates. In the fiber direction, the thermal conductivity doubled from ~3 W/mK for the uncoated fiber, to ~6 W/mK for the nickel, and increased six times to ~20 W/mK for the copper-coated fiber for a fiber volume content of ~50 vol %. Transverse to the fiber, the thermal conductivity increased from 0.6 W/mK (uncoated fiber) to 0.9 W/mK (nickel) and 2.9 W/mK (copper) at the same fiber content. In addition, the electrical conductivity could be enhanced to up to ~1500 S/m with the use of the nickel-coated fiber. We showed that the flexural strength and modulus were in the range of the uncoated fibers, which offers the possibility to use them for lightning strike protection, for heatsinks in electronics or other structural heat transfer elements.